Avaliação in vitro da atividade antimicrobiana de extratos de fundos endofíticos em frente a cepas presentes nas infecções endodônticas - (:unkn) unknown (Universidade Federal do Amazonas, 2009)
The persistence of bacteria inside the root canal system after the chemical-mechanical preparation has been considered the main etiological cause of maintenance or appearance of refractory lesions. Biodiversity of endophytic fungi in the Brazilian Amazon may be natural source of new antibiotics to control microorganisms in Endodontics. This study evaluated 101 extracts from endophytic fungi isolated from Amazon plants such as Victoria amazonica, Rollinia sp. and Duguetia stelechantha about potential antibiotic against endodontic strains. Were tested by the agar diffusion method, extracts the concentration of 2 mg/ml against strains of Staphylococcus aureus, Streptococcus mutans, Pseudomonas aeruginosa, Enterococcus faecalis and Candida albicans. The results were analyzed by Kruskal-Wallis and Mann-Whitney test, using Epi-Info 3.5.1. There was formation of halo of inhibition to 18 extracts of V. amazonica. There were no positive results to the extracts of Rollinia sp. and D. stelechantha. Twelve extracts were positive for S. aureus with the highest average of 14 mm, with no statistical difference between means (p = 0.986). Six extracts inhibited the growth of S. mutans and the best average of 14 mm, with statistical difference (p = 0.012). Two extracts inhibited the growth of P. aeruginosa with an average of 18 mm, with no statistical difference (p = 0.998). No extract was able to inhibit the growth of E. faecalis and C. albicans. There was no difference between the sizes of halos in the times of 24, 48 or 72 hours. The 18 extracts of V. amazonica and 4 fractions were subjected to autobiography, which showed positive result for one extract against S. mutans and one extract for P. aeruginosa. Three fractions showed activity against P. aeruginosa. For the 2 extracts and 3 fractions with positive results was conducted the test for determining the minimum inhibitory concentration (MIC). The fraction TC4 (ActoEt / MeOH 1: 1) showed activity of 250 µg/ml against the P. aeruginosa. The study revealed that there is potential to be exploited within the diversity of endophytic fungi that can be found in the Amazon region. Additional studies with extracts of V. amazonica must be made in an attempt to obtain a pure substance.
Keywords: Endodontia; Fungos endofíticos; Plantas amazônicas; Victoria amazonica; Vitória régia; CIÊNCIAS DA SAÚDE